Systematic literature review: Implementation of STEM-based learning approach on students' interest in biology - Indah Pujiati TM; Vinna Widayati; Slamet Suyanto; Habibah Nurfaizah Azra (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Student interest in STEM-based biology learning is essential to support the development of science and technology, yet the trends and dynamics of this interest over seven decades have not been mapped in depth. This study analyzes students' interest in biology learning through the STEM approach over seven decades using Scopus data, offering valuable insights for biology education at all educational levels. The study utilizes a systematic literature review (SLR) method, adapted from the PRISMA model. The SLR findings reveal that interest and persistence in STEM learning peaked in 2022, particularly in Indonesia and the United States. In Indonesia, biology education faces challenges such as outdated curricula, lack of resources, and insufficient teacher training, which decrease student motivation. The STEM approach can address these issues by integrating biology with technology, engineering, and mathematics, allowing students to see real-world applications and enhancing engagement in learning. The study suggests aligning biology education with the STEM approach, which can be applied across all science subjects, making learning more meaningful and boosting students' interest. STEM is included in this SLR due to its importance in education, as it helps engage students in science education and provides supportive conditions for their interests to grow. The ultimate goal is to make science education accessible to all learners in the 21st century, fostering an environment that encourages curiosity, creativity, and critical thinking.Abstrak. Minat siswa dalam pembelajaran biologi berbasis STEM sangat penting untuk mendukung perkembangan sains dan teknologi, namun tren dan dinamika minat ini selama tujuh dekade belum dipetakan secara mendalam. Penelitian ini bertujuan untuk menganalisis minat siswa dalam pembelajaran biologi dengan pendekatan STEM selama tujuh dekade, menggunakan data dari Scopus, yang akan memberikan wawasan berharga bagi pendidikan biologi di semua tingkat pendidikan. Penelitian ini menggunakan metode tinjauan literatur sistematis (SLR) yang diadaptasi dari model PRISMA. Hasil SLR ini mengungkapkan beberapa temuan menarik, termasuk fakta bahwa minat dan ketekunan dalam pembelajaran STEM mencapai puncaknya pada tahun 2022, khususnya di Indonesia dan Amerika Serikat. Di Indonesia, pendidikan biologi menghadapi tantangan seperti kurikulum yang sudah ketinggalan zaman, kurangnya sumber daya, dan pelatihan guru yang tidak memadai, yang menurunkan motivasi siswa. Pendekatan STEM dapat mengatasi masalah ini dengan mengintegrasikan biologi dengan teknologi, teknik, dan matematika, sehingga siswa dapat melihat aplikasi di dunia nyata dan meningkatkan keterlibatan dalam pembelajaran. Penelitian ini menyarankan untuk menyelaraskan pendidikan biologi dengan pendekatan STEM, yang dapat diterapkan di semua mata pelajaran sains, membuat pembelajaran lebih bermakna dan meningkatkan minat siswa. STEM dimasukkan dalam SLR ini karena pentingnya STEM dalam pendidikan, karena STEM membantu melibatkan siswa dalam pendidikan sains dan menyediakan kondisi yang mendukung agar minat mereka tumbuh. Tujuan utamanya adalah membuat pendidikan sains dapat diakses oleh semua siswa di abad ke-21, menumbuhkan lingkungan yang mendorong keingintahuan, kreativitas, dan pemikiran kritis.